Tragedi Kanjuruhan dalam Perspektif Media Timur Tengah - Adi Ahmad Ridwan Fauzi; Dimas Prakoso Nugroho (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. On October 1, 2022, there were riots and incidents after the end of the Indonesian league 1 football match between the Arema FC team and the Persebaya team in the 11th week of the 2022-2023 league 1 season at the Kanjuruhan Stadium in Malang Regency, East Java. The tragedy that claimed 754 people, including 132 dead, 26 seriously injured and 596 slightly or moderately injured, caused deep sorrow for the victims, their families, and the people of Indonesia. This news is taken from the Middle East news website, Al Jazeera. From this background, the researcher took the formulation of the problem of how to analyze the framing of kanjuruhan news in the perspective of the middle east media with the aim of knowing how the framing analysis of kanjuruhan news in the perspective of the middle east media. This study uses qualitative research methods with framing analysis allowed by Zhongdang Pan and Gerald M. Kosicki and uses agenda setting media theory introduced by McCombs and DL Shaw. Framing is an important element in the development of news in a media. So if it is concluded as a whole from news 1 to news 3 from Al Jazera side with the community to demand justice and corner only one party, namely the police. Abstrak. Tanggal 1 Oktober 2022 terjadi kerusuhan dan insiden pasca berakhirnya pertandingan sepak bola liga 1 Indonesia antara tim Arema FC dan tim Persebaya pada pekan ke-11 liga 1 musim 2022- 2023 di Stadion Kanjuruhan Kabupaten Malang, Jawa Timur. Tragedi yang merenggut 754 orang, termasuk 132 meninggal dunia, 26 luka berat dan 596 luka ringan atau sedang, menimbulkan kesedihan mendalam bagi para korban, keluarganya, dan masyarakat Indonesia. Pemberitaan ini di ambil dari laman berita Timur Tengah yaitu Al Jazeera. Dari latar belakang tersebut peneliti mengambil rumusan masalah bagaimana analisis framing pemberitaan kanjuruhan dalam prespektif media timur tengah dengan tujuan untuk mengetahui bagaimana analisis framing pemberitaan kanjuruhan dalam prespektif media timur tengah. Penelitian ini menggunakan metode penelitian kualitatif dengan analisis framing yang di perkenlkan oleh Zhongdang Pan and Gerald M. Kosicki serta menggunakan teori agenda setting media yang di perkenalkan oleh McCombs dan DL Shaw. Framing menjadi elemen penting dalam perkembangan pemberitaan di suatu media. Sehingga jika disimpulkan secara keseluruhan dari berita 1 hingga berita 3 dari al jazera berpihak kepada masyarakat untuk menuntut keadilan serta menyudutkan satu pihak saja yakni pihak kepolisian.